Особливості формування граничної мастильної плівки на поверхнях тертя гідравлічних машин - Воронін, Сергій Володимирович; Voronin, Serhii (Запоріжжя : Видавничий дім «Гельветика», 2025)
UA: Уточнено механізм утворення граничної мастильної плівки на поверхнях деталей гідравлічних машин. Враховані особливості міцелярної структури присадки в оливі як фактора, що впливає на фізичну адсорбцію полярних молекул. Проведено розрахунок об’ємної концентрації присадки в неполярному розчиннику та виконане її співставлення зі значенням критичної концентрації міцелоутворення. Запропоновано метод інтенсифікації адсорбції присадки шляхом обробки оливи електричним полем. Проведені експериментальні дослідження впливу концентрації присадки та електричної обробки на характер зміни товщини граничної мастильної плівки. Дослідження виконували методом «стовпця кульок» з вимірюванням висоти стовпця до та після змочування. Підтверджено значення критичної концентрації міцелоутворення для обраної присадки, отримані значення концентрації при якій досягається максимум товщини мастильної плівки. /// EN: Based on the concepts of physical and colloidal chemistry, the mechanism of formation of a boundary lubricating film on metal friction surfaces of hydraulic machine parts has been clarified. The features of the supramolecular micellar structure of the additive in the base oil have been taken into account as a factor affecting the process of physical adsorption of surface-active molecules. The volumetric concentration of lauric acid in a non-polar mineral hydrocarbon solvent - industrial base oil - has been calculated. The calculated data have been compared with the value of the critical concentration of micelle formation of lauric acid at the operating temperature of hydraulic oil. It has been established that the real concentration of the additive far exceeds the critical concentration, i.e., additives in modern oils are mainly in a micellar state, which does not contribute to the conditions for effective formation of a lubricating film. A method of intensification of physical adsorption of additive molecules by pre-treatment of the oil with an electric field has been proposed. To confirm the refined mechanism of lubricating film formation and the method of intensification of additive adsorption, experimental studies of the influence of the additive concentration in oil and electrical treatment on the nature of the change in the thickness of the boundary lubricating film were conducted. The studies were performed using the “column of balls” method by wetting the balls with the oil under study and measuring the height of the column before and after wetting. A different nature of the change in the film thickness was established depending on the additive concentration for oil without electrical treatment and with treatment. The value of the critical concentration of micelle formation for the selected additive at a given temperature was experimentally confirmed, and the concentration values at which the maximum thickness of the lubricating film is achieved were obtained.
Features of the Formation of a Boundary Lubricant Film on Friction Surfaces of Hydraulic Machines
Keywords: гідравлічна олива; присадка; міцела; мастильна плівка; електричне поле; hydraulic oil; additive; micelle; lubricating film; electric field